Simulation of Land Use/Land Cover Dynamics Using Google Earth Data and Qgis: A Case Study on Outer Ring Road, Southern India - Saavedra-Flores, E (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The land use and land cover change dynamics is in par with the increasing growth of urban developments and associated sprawl. The objective of the study is to quantify such land cover changes caused due to the urban expansion along the outer ring road using Remote Sensing and GIS. The land cover maps are created for four segments namely Chikkarayapuram, Nazarathpettai, Meppur, and Perungalathur for the years of 2009, 2012, and 2016, respectively. The land cover maps are analyzed for changes among seven classes, namely agriculture, barren land, residential units, industry, water body, other vegetation, and marshland (swamp). Further, the land cover maps of the four segments are analyzed for changes in terms of spatiotemporal aspects (area-based land cover change), environmental aspects (green cover change), and economical factors. The urban growth of the Chikkarayapuram, Nazarathpettai, Meppur, and Perungalathur segment along the outer ring road corridor in the years 2009, 2012, and 2016 are (5.16%, 20.10%, 7.14%, and 12.63%), (14.31%, 30.62%, 13.9%, and 22.18%), and (19.67%, 33.1%, 23.22%, and 40.27%), respectively. The urban areas have increased from 2009 to 2016 by 20, 76,530 sq. m. The agriculture regions have been reduced from 2009 to 2016 by 12, 62,700 sq. m. Besides, using the MOLUSCE plugin in open-source GIS (QGIS), simulated maps for the year 2022 were created based on the land cover maps of the three years (2009, 2012, and 2016) which are then validated with the ground-truth points obtained from Google Earth. The scope of the study utilization of Google Earth Engine (GEE) and automated feature extraction algorithms for predictive analysis. © 2022 by the authors.